Estudo meta-analítico das interações produtivas e nutricionais das micotoxinas na alimentação de suínos e frangos de corte - Andretta, Ines (2011)
Two studies were performed in order to evaluate, through meta-analysis, the relationship of mycotoxins with performance and organ weights in pigs and broilers. The databases totaled 13,196 pigs (85 articles published between 1968 and 2010) and 37,371 broilers (98 articles, between 1980 and 2009). Meta-analysis followed three sequential analyses: graphical, correlation and variance-covariance. Pigs challenged by mycotoxins reduced feed intake by 18% and weight gain by 21% in relation to the control group. Challenged broilers presented a reduction of 12% in feed intake and 14% in weight gain. Mycotoxins with the greatest impact on performance were deoxynivalenol and aflatoxins in pigs, and ochratoxins and aflatoxins in broilers. The mycotoxin concentration in diets and the animal age at challenge were the variables that more improved the coefficient of determination in equations for estimating the mycotoxin effect on weight gain. The mycotoxin effect on growth was greater in younger animals. In addition, the residual analysis demonstrated that the greater part of the variation in weight gain was explained by the variation in the feed intake (87% in pigs and 65% in broilers). The variation in weight gain in challenged animals was also influenced by nutrient ingestion, such as protein and methionine. The mycotoxin effect on growth was greater in male pigs (-19%) compared to females (-15%). Mortality rate and some hematological parameters were also influenced by mycotoxins in broilers. Relative weight of organs increased in challenged pigs (liver, kidneys and heart) and broilers (liver, kidneys, lungs and gizzard). Mycotoxins influence on performance, productive indexes and organ weight in pigs and broilers. However, the magnitude of the effects varies with the type and concentration of mycotoxin, sex and age of the animal, as well as nutritional factors.